2014
DOI: 10.1097/mph.0b013e3182a11676
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Human Herpesvirus 6 Reactivation and its Relationship With Syndrome of Inappropriate Antidiuretic Hormone Secretion After Stem Cell Transplantation in Pediatric Patients

Abstract: There have been several reports on the reactivation of human herpesvirus 6 (HHV6) after stem cell transplantation (SCT) in adults, which sometimes induces severe illness. Few reports exist on pediatric patients; therefore, we retrospectively examined HHV6 reactivation after SCT in children. We reviewed 80 patients with a median age of 6 years. We analyzed HHV6 DNA serum samples from the patients before SCT and at 20 and 40 days after SCT using polymerase chain reaction. We also analyzed the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Whereas even intractable CMV, EBV, and AdV infections have proved to be responsive to adoptive T cell transfer (3)(4)(5)(6)(7)(8)(9)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), neither BKV nor HHV6, both of which may cause severe and intractable disease in HSCT recipients (33)(34)(35)(36)(37)(38)(39), had previously been targeted using this approach. BKV is a ubiquitous polyomavirus that establishes a latent, asymptomatic infection in >90% of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas even intractable CMV, EBV, and AdV infections have proved to be responsive to adoptive T cell transfer (3)(4)(5)(6)(7)(8)(9)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), neither BKV nor HHV6, both of which may cause severe and intractable disease in HSCT recipients (33)(34)(35)(36)(37)(38)(39), had previously been targeted using this approach. BKV is a ubiquitous polyomavirus that establishes a latent, asymptomatic infection in >90% of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] HHV-6 encephalitis may accompany syndrome of inappropriate antidiuretic hormone. [38][39][40] HHV-6 encephalitis typically shows an MRI signature of hyperintense lesions on T2-weighted, fluid-attenuated inversion recovery imaging and diffusion-weighted imaging of bilateral medial temporal lobes, primarily affecting the hippocampus and amygdala (Figure 1). 3,7,[36][37][38]41,42 Some investigators have termed this finding 'post-transplant acute limbic encephalitis (PALE) 38,40,[42][43][44] and HHV-6 PALE has been diagnosed when the patient has detectable HHV-6 DNA in cerebrospinal fluid in the context of acute-onset altered mental status, amnesia, seizures or other evidence of medial temporal lobe disease involving the limbic system and no other identifiable etiology.…”
Section: Disease Associations: We Do Not Know the Precise Disease Assmentioning
confidence: 99%
“…38 The syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is the most de nitely documented pathogenesis of hyponatremia after allo-HSCT 22,38,39 and was reported the association with HHV-6 encephalitis. 20,40,41 Although not all cases had been tested to formally diagnose SIADH in this study, 2 out of 14 patients with HHV-6 encephalitis and 1 out of 120 patients without HHV-6 encephalitis were diagnosed with SIADH. Regarding the timing of hyponatremia and HHV-6 encephalitis, Murakami et al reported that all 5 patients with HHV-6 encephalitis showed hyponatremia on or a few days before the onset.…”
Section: Discussionmentioning
confidence: 93%